Morcegos em florestas tropicais secas brasileiras - Luiz Alberto Dolabela Falcão (2015)
Bats play a fundamental role in ecosystem functioning, as they are responsible for several ecological services, such as seed dispersal and pollination. Hence, assessing the effects of habitat structure at different scales on the bat community is extremely important to support conservation strategies. The objective of the present study was to investigate the effects of habitat structure at multiple spatial scales on the bat communities and its variation along a gradient of secondary succession in a Brazilian tropical dry forest. Our results suggest that bat abundance is higher in areas close to mature forests, which shows the important role of those habitats as refuges for the regional bat fauna (in a fragmented landscape) and for the maintenance of ecosystem services provided by this group in tropical dry forests in a landscape context. In addition, bat abundance was lower in protected areas whose surroundings were better protected (higher amount of forests). This unexpected finding could result from altered behavior in areas under a strong influence of a fruit crop matrix, showing the effects of this type of matrix on bat diversity.